Οι νηπιαγωγοί και η προβληματική συμπεριφορά του νηπίου στο σχολείο: Πώς την αντιλαμβάνονται και πώς την αντιμετωπίζουν - Γαλανάκη, Ε. (Μακεδνόν: Περιοδική επιστημονική έκδοση της Παιδαγωγικής Σχολής Φλώρινας του ΑΠΘ, 2002)
The aim of the present study was to investigate a) which kinds of the infant's behaviour kindergarten teachers identify most often as problem behaviour, and b) which kinds of interventions teachers implement to deal with the problem behaviours. Although there is a large body of research on this issue concerning elementary and high-school teachers, this is not the case for kindergarten teachers. The sample consisted of 131 kindergarten teachers from a post-training program at the University of Athens. They were asked to describe in written form a recent problem behaviour of an infant in their school and the interventions they tried. The qualitative and quantitative analyses of the written descriptions revealed the most common problem behaviours of the infants from the teacher’s viewpoint, and the corresponding interventions. The way kindergarten teachers describe the infant’s problem behaviour, the way they organize their interventions, the quality of the interventions, the teachers’ attitudes toward the effectiveness of their interventions, as well as their overall attitudes toward the problem behaviour are discussed and interpreted in light of their implications for teacher education and counseling programs.